UNBOXING NEW MASCULINITY: ANALYSING KEN’S EVOLUTION IN BARBIE’23 - Nousheen, Javairia; Prajapati, Abhisarika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The representation of masculinity in media has long been dominated by traditional stereotypes, perpetuating rigid gender norms, and limiting the scope of diverse expressions of male identity. However, the film "Barbie" which recently released starring Margot Robbie as Barbie and Ryan Gosling as Ken presents a refreshing departure from this norm by offering an intriguing portrayal of Ken, a character with a rich history in popular culture. This research paper examines how the movie reimagines and challenges conventional notions of masculinity through Ken’s character arc. The paper shall establish the historical context of Ken’s portrayal in previous Barbie movies and merchandise, where he often embodied the archetypal male figure, emphasizing physical appearance and material possessions. Through a comprehensive analysis of "Barbie’23," the study explores how the film deconstructs these stereotypes and reconstructs Ken as a multifaceted and relatable character, embracing a broader spectrum of masculinity. Key themes explored include Ken’s journey of self-discovery, emotional intelligence, and vulnerability. "Unboxing New Masculinity: Analysing Ken’s Evolution in Barbie’23" seeks to contribute to ongoing conversations about reimagining masculinity in media and highlights the importance of inclusive storytelling for young viewers. By breaking away from the traditional mold, "Barbie’23" exemplifies a forward-thinking narrative that paves the way for a more accepting and diverse portrayal of masculinity in children’s entertainment.